Sanksi Pidana Terhadap Oknum Kepala Desa Sebagai Pelaku Tindak Pidana Korupsi Dana Desa: Studi Kasus Putusan Pengadilan Nomor 99/Pid.Sus/2013/Pn.Mks - Fakhlur; Rochmad (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2021)
Recently, the spotlight on corruption in Indonesia has been associated with development funds or projects for the procurement of goods and services, therefore whatever the reason, whether it is intentional or unintentional due to procedural or system errors, but ultimately results in financial losses to the country, it can be said that it is a crime. acts of corruption. In this study, the authors provide examples of cases of abuse of authority by the village head against village funds that should be used for drainage construction, but are used for personal interests. The case has been decided by the Makassar District Court with its decision Number 99/Pid.Sus/2013/PN Mks, and the defendant has been sentenced to criminal sanctions with imprisonment for 1 (one) year and a fine of Rp. 50,000,000, - (fifty million rupiah). The formulation of the problems discussed by the author are: 1) How is the legal arrangement of village funds managed for the welfare of the village community? and 2) What are the criminal sanctions against perpetrators of corruption in village funds in the decision of the Makassar District Court Number: 99/Pid.Sus/2013/PN.Mks?. The research method that the author uses is the normative juridical method, which is to analyze the relationship between the applicable laws and regulations with legal theories and the practice of implementing positive law concerning the issues discussed. Finally, the author concludes that the legal regulation of village funds that are managed for the welfare of rural communities is by referring to Government Regulation Number 47 of 2015 concerning Amendments to Government Regulation Number 43 of 2014 concerning Implementing Regulations of Law Number 6 of 2014 concerning Villages and Guidelines for the Use of Funds. This 2020 Village is guided by the Provincial Government, Regency / City Government, and Village in managing priorities for the use of Village Funds based on democratic village governance and social justice.